Artificial Heart 3 Proceedings of the 3rd International Symposium on Artificial Heart and Assist Devices, February 16–17, 1990, Tokyo, Japan - Akutsu, Tetsuzo; Koyanagi, Hitoshi; Anderson, James M.; Cohn, Lawrence H. (Springer Japan, 1991)
The International Symposium on Artificial Heart and Assist Devices has been held three times, first in 1985, then in 1987 and 1990. It is my great pleasure to present Artificial Heart 3 (Proceedings of the 3rd International Symposium on Artificial Heart and Assist Devices). The third symposium was held in Tokyo on February 16 and 17, 1990. Our original intention was to invite all the principal investigators from the major artificial heart research laboratories in the world, in the first three symposia. The numbers of investigators in the fields of the artificial heart, ventricular assist systems, and biomaterials, invited for the symposia, totalled 7 in 1985, 8 in 1987, and 13 in 1990. The program of the third symposium consisted of 41 papers; 13 invited lectures, 8 papers contributed upon request, with 2 from the United States, and 20 regular selected papers including 2 from the United States, ana 1 each from Australia, Germany, and South Korea. During the last three years, the state of clinical application of artificial hearts and assist devices has changed. In the case of pneumatically driven blood pumps, we have now stepped into the age of practical use in patients. Accordingly, in this symposium we gave a special emphasis to topics of clinical application, particularly the use of an artificial heart as a bridge to heart transplantation. Sessions on implantable artificial hearts, biomaterials for the artificial heart, and heart transplantation were also included